포도 흰송이 증상과 관련된 Hanseniaspora(Kloeckera) sp.의 분리 및 동정 - 이예령(Yeryeong Lee); 김근곤(Geun Gon Kim); 정영륜(Young Ryun Chung) (Sigmulbyeong yeon'gu, 2005)
An epidemic of the white dusty covering of grape clusters and canes by dust-like particles occurred in many vineyards near Gimcheon, Gyeongbuk area since 2000. Although the covering was severe, it seldom resulted in appreciable damage to vine health except drastical reduction of grape quality. It appears that the abnormal growth of a resident yeast Hanseniaspora (Kloeckera) sp. is related to the white dusty covering on the grape surface. 최근 수년간 김천지역 대부분의 포도 과수원에 심하게 발생되었던 일명 '흰송이' 증상을 나타내는 흰가루의 주 미생물은 포도 표면에 존재하면서 포도주 발효시 중요한 문제를 일으키는 효모균 Hanseniaspora (Kloeckera) sp.으로 동정되었으며, 이러한 증상의 발생은 과도하게 사용된 당분과 관련이 있을 것으로 생각된다.